Online instrument systems in reality for remote wiring and measurement of electronic in e-learning from LabVIEW+NI ELVIS II vs embedded system+web services - Fahd Ouatik; Mustapha Raoufi; Farouk Ouatik; Mohammed Skouri (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Recently The prestigious universities of the world strive and aim to computerize their distance education service and more specifically the remote practical work, which allows students to manipulate electronic experiments via the web, for to solve a set of problems: pedagogical, management, security, restriction by time and place and the problems the overcrowding of students in universities. This paper will describe the E@SLab system developed by the university Cadi Ayyad member of the e-live project funded by EU in the frame of ERASMUS+E@SLab is based on the latest technologies of development and respects educational and pedagogical standards. E@SLab offers 2 versions different of remote laboratory: first version (s1) is an embedded system its part software is node js+Ubuntu and the part hardware a card pcduino or raspebery. The second version (s2) is based on LABview and its hardware part is the NI ELVIS II pedagogical map. In this paper, we will compare and discuss the architecture, performance of the 2 versions of E@SLAB and review other famous approaches NetLab, VISIR, for comparing with E@SLab with the intention show its singularity.